Patient Risks From Human Error in Medical Record Management - Albertus Dhaja; Lusy Kezia Purba; Maria Franciska K. Dewi; Nadila Fitriana; Rika Ayu Novitasari (PT. Caesarindo Triloka Persada, 2025)
This study investigates the risks faced by patients as a result of human errors committed by medical record officers in the context of Indonesian healthcare institutions. While previous research has explored the impact of administrative mistakes in medical recordkeeping, few have analyzed their legal and clinical consequences within a rapidly digitalizing healthcare system. This research addresses that gap by evaluating both the causes and effects of human error, particularly during the transition from manual to electronic medical records mandated by the Ministry of Health. Using a qualitative literature review method, this study synthesizes data from various international and national studies conducted between 2020 and 2025. The analysis reveals that human errors stem from individual factors such as fatigue and insufficient training, systemic factors like incomplete standard operating procedures and high workloads, and institutional issues involving poor supervision and punitive organizational culture. These errors not only jeopardize patient safety—leading to misdiagnosis, treatment delays, and privacy breaches—but also expose staff to legal and professional sanctions. The study contributes a novel perspective by integrating legal risk analysis with human factors in medical record management, emphasizing the urgent need for multidimensional policy reforms and continuous professional training to safeguard both patients and healthcare providers.